Fake news and post-truth worlds: which democracy at stake? - Santos, Nina (2020)
Fake news and post-truth have become current terms on contemporary debate as symbols of threats to democracies. What do Johan Farkas and Jannick Schou do in the book “Post-truth, fake news and democracy. Mapping the politics of falsehood” is to question the idea of democracy that underlies these speeches and to propose a shift in the debate. The authors adopt a post-foundationalist approach to analyze more than 500 texts on fake news and post-truth published between 2015 and 2018. They argue that the criticism of these processes is mostly based on a rational view of democracy, which tends to depoliticize these processes. In arguing that the basis of democratic regimes is not the truth but popular sovereignty, they claim that centering the debate only on regaining of a certain rationality can be a dangerous path for democracies.